PENGARUH PROPORSI TEPUNG RASPBERRY (Rubus rosifolius) DAN TEPUNG BERAS (Oryza sativa L) TERHADAP SIFAT FISIK SEDIAAN KOSMETIKA MASKER BUBUK - Gabriella Septiananda Santoso; Maspiyah; Dewi Lutfiati; Sri Dwiyanti (Journal of Beauty and Cosmetology (JBC), 2024)
The abundant biodiversity is a factor in the development of cosmetic formulations from natural ingredients such as facial masks. Facial masks are cosmetics that can perform cleansing, toning and nourishing. Biological ingredients that can be used to make natural facial mask formulations are raspberries and rice. The purpose of this study was to determine 1) the effect of the proportion of raspberry flour and rice flour on the physical properties of powdered face masks including aroma, color, texture, and adhesion, panelist preferences. 2) the best shelf life of powdered face masks with microbiological tests. This type of research is a pre experiment. The independent variables in this study are the proportions of raspberry flour and rice flour, namely X1 (3: 7), X2 (5: 5), and X3 (7: 3). The dependent variables are physical properties including color, aroma, texture, adhesion, panelist preferences and shelf life. Data collection using the observation method carried out by 30 panelists and microbiological tests to determine the shelf life. Data were analyzed using a single Anova test and continued with Duncan's test using SPSS version 29. The results of the study showed a significant effect on the proportion of face masks X1 with a value of 2,62, X2 with a value of 2,34 and X3 with a value of 2,92. So the conclusion of this study is that the proportion of face masks X3 (7:3) has the best physical properties with an average of 2,92 and the shelf life of face masks X3 can last for 9 days with a total plate of 8,5 x 10^4 CFU/ml.